Relationship Between Level of Knowledge and Nurse Compliance in the Implementation of Standard Operational Procedures (SOP) for Infusing in the Emergency Installation Unit. - Sholehah, Baitus; Holifah, Siti (Fakultas Kesehatan, Universitas Nurul Jadid, 2024)
Introduction: Emergency Department is the main entry point for hospital services in providing first aid to patients. One of the common infections in hospitals is nosocomial infection. The success of controlling nosocomial infections in infusion procedures is not determined by advanced equipment but by the behavior of healthcare workers in properly caring for patients.. Objectives: This study aims to analyze the relationship between knowledge level and nurses' compliance with the Standard Operating Procedure (SOP) for Infusion Placement in the Emergency Department of RSU dr. H. Koesnadi Bondowoso.. Methods: The study was conducted in January 2016 at the Emergency Department of RSU dr. H. Koesnadi Bondowoso. A correlational design with a cross-sectional approach was used. The population consisted of all nurses in the Emergency Department, with a total sample of 18 participants, selected using total sampling technique. Data were collected through questionnaires and observation sheets, then analyzed using SPSS